Conversion Surgery for Pancreatic Cancer—The Impact of Neoadjuvant Treatment - Klaiber, Ulla; Hackert, Thilo (Frontiers in Oncology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) still has a dismal prognosis, mainly because only 15-20% of all patients present with resectable tumors at the time of diagnosis. Upfront resection is not reasonable in the majority of patients due to locally extended tumor growth or distant metastases. PDAC will become the second most frequent cause of cancer-related death for both men and women within the next 10 years. While there is currently no convincing evidence regarding the use of neoadjuvant therapy in resectable PDAC, interesting results have emerged from studies investigating neoadjuvant treatment concepts in borderline resectable PDAC (BR-PDAC). However, the definition of BR-PDAC is a topic of debate. While BR-PDAC was originally defined on merely anatomical criteria, the International Association of Pancreatology has recently suggested a broader definition based on a combination of anatomical (A) findings, biological (B) criteria (which reflect tumor aggressiveness), and conditional (C) aspects (which refer to host-related conditions). In the case of BR-PDAC with venous invasion alone, upfront resection is generally recommended whenever technically possible in patients who are fit for surgery and show no sign of lymph node metastases. In contrast, neoadjuvant therapy is regarded as the treatment of choice in the presence of arterial invasion. The same is true for high CA 19-9 levels, suspected or proven lymph node involvement, and poor performance status. In locally advanced PDAC (LA-PDAC), neoadjuvant treatment represents the standard of care, resulting in relatively high rates of secondary resection. This “conversion” surgery offers the chance of longer survival in an otherwise palliative situation. We summarize here the current evidence on different treatment strategies for pancreatic cancer, with a focus on conversion surgery and the impact of neoadjuvant treatment in this setting.